The trade of Singapore, 1819-69 - Wong, Lin Ken (MBRAS reprint, 2003)
This is a study of the trade of Singapore from the year of its establishment to the year 1869, when the opening of the Suez Canal marked the beginning of a new era of trade between Europe and Asia.